Manajemen Pelatihan Dakwah Santri dalam Menyiapkan Kader Da’i di Pondok Pesantren Ma’ruful Hidayah Kabupaten Garut - Maulana, Ridwan; Setiawan, Asep Iwan; Rustandi, Ridwan (Tadbir: Jurnal Manajemen Dakwah, 2025)
The aim of this research is to determine (1) planning, (2) organizing, (3) actualizing, (4) monitoring and evaluating santri da'wah training in preparing da'i cadres at the Ma'ruful Hidayah Islamic Boarding School. The method used in this research is a qualitative descriptive method. Based on the research results, the management of santri da'wah training at the Ma'ruful Hidayah Islamic boarding school obtained data that: (1) Planning: formulating training objectives, identifying training needs, determining training materials, substituting the training curriculum, and determining the time and schedule for da'wah training; (2) Organizing: organizing missionary training needs, division of work, and forming a missionary training committee; (3) Actualization: implementation of the curriculum, implementation of the training model and formation of a da'wah practice group; (4) Supervision and Evaluation: formative supervision and evaluation of the training committee and summative training participants. So it can be concluded that the management of santri da'wah training in preparing da'i cadres at the Ma'rful Hidayah Islamic boarding school has gone well in producing da'i cadres.